ENTERTAINMENT, INFOMATIVENESS, CREDIBILITY, ATTITUDES TERHADAP PURCHASE INTENTION PADA SUBSCRIBER CHANNEL YOUTUBE - CHRISMANTARA RUBY SETIAWAN; VITA BRILIANA (Jurnal Bisnis dan Akuntansi, 2021)
The purpose of this study was to determine the effect of entertainment, informativeness, credibility, and attitudes towards purchasing intentions of Deddy Corbuzier's YouTube channel viewers for products advertised in YouTube podcasts. The sampling technique used purposive sampling using a sample of 212 respondents whose data were processed using SmartPLS 3.0 and IBM SPSS 25. The results showed that all variables (entertainment, informativeness, credibility, and attitude) had a significant effect on purchase intentions.